BAITUL MAL ACEH IN THE ISLAMIC PUBLIC FINANCIAL FRAME - Nurdiana Sari Nurdin (SHIBGHAH: Journal of Muslim Societies, 2020)
This study intends to analyze the role of Baitul Mal Aceh in managing public finances. Given its very significant role, the Baitul Mal Aceh has the opportunity to be able to re-implement the Baitul Malfunction as in the heyday of Islam. The research method used is the library method with descriptive analysis. The results showed that the Baitul Mal Aceh was given the authority to manage and develop zakat, endowments, religious assets to benefit the Ummah and to become trustees/guardians of orphans and/or their assets and to manage inheritance without inheritance based on shari'a at Islam. With the extent of authority granted, Baitul Mal Aceh can be used as a center for regional financial management as a whole without the need for special segregation for the management of religious assets. This institution is like being a special central bank of Aceh and this is a challenge for Baitul Mall, both regulatory readiness and other readiness.